Developing empathy in healthcare professions students: protocol of a mixed-methods non-controlled longitudinal intervention study - Müller, Andre Matthias; Ngiam, Nicola Siew Pei; Dunn, Michael; Samarasekera, Dujeepa D.; Goh, Benjamin Yen Seow; Goh, Charlene En Hui; Toh, Ann; Lee, Jeannette; Yau, Wai-Ping; Lau, Lydia Siew Tang; Gallagher, Paul John (Frontiers in Medicine, 2024)
Despite the necessary focus on clinical skills and knowledge during the tertiary education of healthcare professionals, the literature highlights the importance of developing psycho-social competencies. Empathy, a cognitive-behavioral attribute linked to various benefits for patients and healthcare professionals, is one such competency. Pedagogical approaches to successfully develop empathy in tertiary healthcare students are available. However, these approaches are often integrated piecemeal throughout the tertiary education journey. Research on a more empathy-focused curriculum is scarce. This manuscript describes the design of a study that aims to examine the effects of a more empathy-focused curriculum on empathy in tertiary healthcare profession students in Singapore. Freshmen dentistry, medicine, nursing, and pharmacy students enrolled in a novel curriculum with a strong empathy focus will be recruited for the study and followed for the program’s extent. Mixed-methods data collection at various time points will be conducted. Quantitative data will be collected on cognitive-behavioral empathy, intentions to provide empathic care, and engagement in courses of the curriculum. Qualitative data on perceptions of patient care and empathy in relation to relevant courses of the curriculum will be collected to provide context for quantitative findings. Ethics approval was granted by the Departmental Ethics Review Committee of the Saw Swee Hock School of Public Health, National University of Singapore (Ethics ID: SSHSPH-214).